Identification of diarrheagenic Escherichia coli by a new multiplex PCR assay and capillary electrophoresis. (February 2020) - Zhang, Jingyun; Xu, Yang; Ling, Xia; Zhou, Yongming; Lin, Zheng; Huang, Zheng; Guan, Hongxia; Xiao, Yong; Xu, Wen; Kan, Biao
Abstract: Diarrheagenic Escherichia coli (DEC) is a set of the most common pathogens causing diarrhea. DEC strains are classified into five pathotypes based on the possession of different virulence genes: enteropathogenic E. coli (EPEC), enterohemorrhagic E. coli (EHEC) or Shiga toxin-producing E. coli (STEC), enteroaggregative E. coli (EAEC), enterotoxigenic E. coli (ETEC), and enteroinvasive E. coli (EIEC). The development of an easy-to-use method to detect the specific virulence genes and distinguish the pathotypes is essential for the diagnosis and surveillance of DEC infections. In this study, a multiplex PCR assay (mPCR) specific to nine virulence genes and an internal control was designed for the identification of five DEC pathotypes. A temperature switch PCR (TSP) strategy was used in the PCR amplification. The PCR products were detected by capillary electrophoresis. The limit of detection (LOD) of the 10-plex reaction was 5 × 10 3 copies/reaction for stx2 and 5 × 10 2 copies/reaction for the other targets. The mPCR showed very high specificity, and inclusivity and exclusivity were both 100%. When the mPCR assay was used for the detection of 221 cryopreserved diarrhea specimens, DEC colonies were detected from 49 specimens, and the positive rate was 22.2%. The mPCR assay was sensitive and specific, and the amplified product could be analyzed easily. Thus, this method could be used effectively to identify the suspected colonies of DEC in the primary culture of the specimen. Highlights: Nine virulence genes of five DEC pathotypes can be detected in one reaction. Capillary electrophoresis analysis makes the reading of the results easier. The assay is sensitive and specific and could identify the suspected colonies of DEC.